Promoting multilingualism and interculturality - Kodba, Maggie Martina (Sodobna pedagogika, 2026)
Migration is changing education systems worldwide. Due to its geographical location, Slovenia serves as a crossroads of different cultures, attracting immigrants, especially from countries of the former Yugoslavia. Despite the linguistic similarities among South Slavic languages, learning Slovenian can be challenging. International and national education policies emphasise the importance of multilingualism and inclusion; however, implementation is often complex in practice. For example, Slovenian legislation supports learning Slovenian for students and third-country adults but not for adult European Union (EU) citizens, while the preservation of immigrants’ mother tongue depends on local school practices and teachers’ qualifications and social attitudes towards immigrants. To address these differences in access and support, and in line with the Common European Framework of Reference for Languages, we developed the Slovify application to improve access and enable initial Slovenian learning for students and other adult Croatian speakers. Besides language learning, Slovify also includes content that familiarises users with Slovenian culture, social norms, and the integration process in a new environment. By combining digital innovations and linguistic and cultural adaptability and by considering global pedagogical standards, the Slovify application is an example of good practice in how educational technology can support inclusion, overcome intercultural barriers, and encourage cooperation.
Keywords: aplikacije; inclusion of immigrants; inkluzija priseljencev; mobile learning; mobilno učenje; pouk drugega jezika; second language acquisition; Slovenščina; Slovify